Hematopoietic Differentiation of Human Pluripotent Stem Cells: HOX and GATA Transcription Factors as Master Regulators - Alsayegh, Khaled; Cortés-Medina, Lorena V.; Ramos-Mandujano, Gerardo; Badraiq, Heba; Li, Mo (Current genomics, 2019)
Numerous human disorders of the blood system would directly or indirectly benefit from therapeutic approaches that reconstitute the hematopoietic system. Hematopoietic stem cells (HSCs), either from matched donors or ex vivo manipulated autologous tissues, are the most used cellular source of cell therapy for a wide range of disorders. Due to the scarcity of matched donors and the difficulty of ex vivo expansion of HSCs, there is a growing interest in harnessing the potential of pluripotent stem cells (PSCs) as a de novo source of HSCs. PSCs make an ideal source of cells for regenerative medicine in general and for treating blood disorders in particular because they could expand indefinitely in culture and differentiate to any cell type in the body. However, advancement in deriving functional HSCs from PSCs has been slow. This is partly due to an incomplete understanding of the molecular mechanisms underlying normal hematopoiesis. In this review, we discuss the latest efforts to generate human PSC (hPSC)-derived HSCs capable of long-term engraftment. We review the regulation of the key transcription factors (TFs) in hematopoiesis and hematopoietic differentiation, the Homeobox (HOX) and GATA genes, and the interplay between them and microRNAs. We also propose that precise control of these master regulators during the course of hematopoietic differentiation is key to achieving functional hPSC-derived HSCs.